Casting and Constitutive Hot Flow Behavior of Medium-Mn Automotive Steel with Nb as Microalloying - Perla Julieta Cerda Vázquez; José Sergio Pacheco-Cedeño; Mitsuo Osvaldo Ramos-Azpeitia; Pedro Garnica-González; Vicente Garibay-Febles; Joel Moreno-Palmerin; José de Jesús Cruz-Rivera; José Luis Hernández-Rivera (Metals, 2020)
A novel medium-Mn steel microstructure with 0.1 wt.% Nb was designed using Thermo-Calc and JMatPro thermodynamic simulation software. The pseudo-binary equilibrium phase diagram and time−temperature transformation (TTT) and continuous cooling transformation (CCT) diagrams were simulated in order to analyze the evolution of equilibrium phases during solidification and homogenization heat treatment. Subsequently, the steel was cast in a vacuum induction furnace with the composition selected from simulations. The specimens were heat-treated at 1200 °C and water-quenched. The results of the simulations were compared to the experimental results. The microstructure was characterized using optical microscopy (OM) and scanning electron microscopy (SEM). We found that the as-cast microstructure consisted mainly of a mixture of martensite, ferrite, and a low amount of austenite, while the microstructure in the homogenization condition corresponded to martensite and retained austenite, which was verified by X-ray diffraction tests. In order to design further production stages of the steel, the homogenized samples were subjected to hot compression testing to determine their plastic flow behavior, employing deformation rates of 0.083 and 0.83 s−1, and temperatures of 800 and 950 °C.